2016
DOI: 10.1016/j.tube.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive sequence specific qPCR detection of Mycobacterium tuberculosis complex in respiratory specimens

Abstract: Nucleic acid amplification tests for Mycobacterium tuberculosis (MTB) detection from sputum are highly sensitive and specific with smear microscopy positive specimens, but their sensitivity with smear-negative/culture-positive specimens is much lower; therefore, these tests cannot rule out a tuberculosis diagnosis. Co-extraction of PCR inhibitors may be a cause of decreased test sensitivity. Here the design and early validation of a MTB screening assay with sample preparation and qPCR methods designed to speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…The sequence specific capture probes and qPCR oligonucleotides were optimized for Tm, and the amount of NaCl was increased from 250 mM to 500 mM to enhance sequence specific capture of MTB DNA 11 . To estimate the limit of detection, 1 ml sputum specimens were contrived to contain 20, 10 or 5 cfu/ml of MTB H37Ra which has 17 copies of IS 6110 16 , and 20 replicates of each concentration were assayed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sequence specific capture probes and qPCR oligonucleotides were optimized for Tm, and the amount of NaCl was increased from 250 mM to 500 mM to enhance sequence specific capture of MTB DNA 11 . To estimate the limit of detection, 1 ml sputum specimens were contrived to contain 20, 10 or 5 cfu/ml of MTB H37Ra which has 17 copies of IS 6110 16 , and 20 replicates of each concentration were assayed.…”
Section: Resultsmentioning
confidence: 99%
“…The limit of detection of the test was estimated to be 20 cfu/ml which is significantly lower than the Xpert® MTB/RIF assay, and no amplification was observed from a panel of 6 NTM species. In a preliminary field study of 60 de-identified blinded sputa, a test sensitivity of 96% and specificity of 100% was observed when compared to the Xpert® MTB/RIF assay 11 . The DNA capture probes and qPCR primers have been optimized for greater analytical sensitivity, and we hypothesize that this novel diagnostic test, hereby entitled XtracTB Assay, will result in improved sensitivity with SSM− specimens over current TB diagnostics.
Figure 1Schematic of sequence specific capture work flow: six steps, Thin, Lyse & Melt, Hybridize, Bind, Wash and Elute are indicated with corresponding times and temperatures detailed.
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflex genotypic drug resistance testing of patients with a positive TB test is an alternative strategy to up-front resistance testing for all patients. Possible strategies to improve sensitivity include nucleic acid extraction from the full sample volume, use of DNA baits to preferentially extract M. tuberculosis DNA [13], use of all of the extracted nucleic acid in the amplification reaction, nested amplification and detection of multiple and multicopy targets.…”
mentioning
confidence: 99%